Application of Eucheuma Cottonii Carrageenan as an Emulsifier in the Making of Mosquito Repellent Lotion from Clove Leaf Essential Oil (Syzigium Aromaticum) - Nurhayati, Nurhayati; Natsir, Hasnah; Raya, Indah; Taba, Paulina; Wahid Wahab, Abdul; Rasyid, Herlina; Irfandi, Rizal (Trends in Sciences, 2025)
Dengue fever in Indonesia continues to increase every year. One form of prevention is the utilisation of clove leaf essential oil (Syzigium aromaticum) as an anti-mosquito lotion. The abundance of Eucheuma cottonii in Indonesia has the potential to increase the production of carrageenan which can function as an emulsifier for lotions. The objectives of this research to analyze the characteristics and effectiveness of anti-mosquito lotion from clove leaf essential oil with the addition of carrageenan based on red algae E. cottonii. The method used was carrageenan extraction with 0.1 N KOH solvent, antimicrobial test with disc diffusion method and antimosquito effectiveness test. Analysis of carrageenan using FTIR showed the presence of galactose 4-sulfate functional group which identified kappa type in the spectrum of 846 - 927 cm–1. Microstructure characteristics of carrageenan using SEM 2000× magnification showed a rough surface and irregular clumps. Characterization of clove leaf essential oil (Syzigium aromaticum) using GC-MS instrument showed the main content of the compound 4.allyl-2-methoxyphenol with an area of 78.89% which includes eugenol compounds. The optimal anti-mosquito lotion was F2 with 4% carrageenan and 15% clove leaves assential oil. Formula 2 has a level of liking in the sensory test in the neutral category, but has good effectiveness with the support of several characteristics that meet quality standards including a pH value of 7.1, a viscosity value of 5,481.8 cP, a moisture content of 4.91% and microbial inhibition of E. coli and S. aureus at a good concentration of 40%. HIGHLIGHTS This article provides a critical review of the use of anti-mosquito lotion made from clove leaf essential oil The production of such lotions is expected to reduce the use of chemicals in health products, particularly those intended for use on human skin Eugenol in clove leaves is reported to have great potential as a mosquito repellent The neurotoxic properties of eugenol suppress the the insect nervous system, resulting in a weakened body. GRAPHICAL ABSTRACT